Laser thermography of weld - process optimization and evaluation - Gan, Kenny (2017)
Infrared thermography is of the most common and widely used Non-destructive technique throughout many years for a reliable and fast inspection of defects. In recent years, a new infrared thermography technique has developed based on the use of laser as an external excitation heat source other than conventional heat source such as flash lamp and halogen lamp. This new technique uses the same principle as other infrared thermography and has been widely used for the detection of defect on flat specimen surface. The focus of this project is to optimized the operating parameter of laser thermography for weld inspection. The project will be conducted in 2 parts, obtaining the optimal parameters using an EDM notch specimen and using the optimal parameters obtained on a welding specimen with root crack. The result are presented on the difference parameter used and how the different parameter affects the accuracy and quality of the thermal images produced.